Draft Annual Plan 1993-94 Andhra Pradesh Volume-II (Sectoral Programmes) 9. Social Services - Planning Commission (Planning Commission, 1992)
The scheduled castes belong to the underprivileged groups and these groups lack adequate opportunities for self-development especially in increasing their income and employment and are deprived of even minimum social services and more specifically facilities in regard to education, health and housing. Constitutional provisions require promotion of their educational and economic interests and efforts to remove their social disabilities and these objectives are to be achieved through planned welfare programmes.
Finance and Planning (PLG. Wing) Departments, Government of Andhra Pradesh